Penerapan Nilai-Nilai Pancasila Terhadap Kehidupan Generasi Muda Di Era Globalisasi - Mutiara Oktaviani Putri; Hasna Lutfi Indriani; Ilham Hudi; Ulviana Agustina; Ersha Wiriani Safitri; Melki Wijaya (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2024)
The aim of this research is to examine how the literature on Pancasila values has developed in the era of globalization. By conducting a literature review and looking at 17 journal articles released between 2019 and 2023. This research aims to convey knowledge or understanding about the application of Pancasila values to the lives of the younger generation in the current era of globalization which has resulted in some people forgetting these values. -value itself. This research shows that most Indonesian people do not apply Pancasila values in their daily lives and the same goes for social life in the era of globalization. This research can be used as a basis for further research in this area and can help increase the awareness of Indonesia's young generation towards the values of Pancasila. Future research could expand the scope and duration of the study, as well as improve the analysis to pinpoint patterns and modifications that need to be considered.